Elmer and the whales [anglicky] - McKee, David (Andersen Press, 2014)
Elmer and his cousin Wilbur decide to go to the coast to see the whales. But their journey becomes far more of an adventure than they find themselves lost at sea. Can the whales help them back to shore.